Wpływ rewolucji cyfrowej na rozwój społeczeństwa informacyjnego oraz społeczną wartość informacji - Skrabacz, Aleksandra; Lewińska-Krzak, Monika (Roczniki nauk społecznych, 2022)
The digital technological revolution has connected the world and dramatically changed the life of modern man. It has become a determinant of the development of society, which has progressed from a post-industrial to an information society, characterized by increased activity in the digital world. The aim of this paper is to characterize the impact of the digital revolution on the growth of the information society and to indicate the key features of this process in the context of the changing value of information and the importance of journalism in the social dimension. The main research problem is: How has the rapid and comprehensive technological advancement influenced the transformation of the post-industrial society into an information society and what consequences these changes have for journalism? We used interdisciplinary research methods. In the theoretical layer, our research was based on the analysis and synthesis of the literature on the subject, as well as induction and deduction, which made it possible to interpret the results of the research logically and draw conclusions. In the empirical layer, we used nationwide and European statistical studies to examine the level of computerization of Polish society in recent years.